Protective effect of ferulic acid against 2,2"²-azobis(2-amidinopropane) dihydrochloride-induced oxidative stress in PC12 cells - Shen, Y; Zhang, H; Wang, L; Qian, H; Qi, Y; Miao, X; Cheng, L; Qi, X (Cellular and Molecular Biology, 2016)
Oxidative stress is closely related to the pathogenesis of neurodegenerative disorders such as Parkinson's disease and Alzheimer's disease. However, the underlying antioxidant mechanisms of ferulic acid (FA) aganist oxidantive stress are poorly understood. We evaluated the potential protective effects of FA against 2,2"²-azobis(2-amidinopropane) dihydrochloride (AAPH)-induced damage in PC12 cells. Our results indicated that pretreatment with FA prior to AAPH exposure significantly increased PC12 cell survival, and also increased catalase and superoxide dismutase activity. Furthermore, FA treatment reduced cellular lactate dehydrogenase release and malondialdehyde levels. It attenuated AAPH-induced apoptosis in PC12 cells, as determined by flow cytometric detection of annexin V. Reductions in mitochondrial membrane potential and accumulation of intracellular Ca2+ were also inhibited by FA treatment. These findings suggested that FA protected PC12 cells against AAPH-induced oxidative stress, and may be a neuroprotective agent.